2020
DOI: 10.5114/pjp.2020.99786
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors of the colon and rectum

Abstract: Gastrointestinal stromal tumors (GISTs) are rare neoplasms, colorectal location being met in less than 5% of cases. Knowledge about this site related particularities are limited. The aim of this study is to present our experience with colorectal GISTs between 2005 and 2018 from the clinical, morphological, and immunohistochemical perspectives, with emphasis on prognostic factors. From a total of 203 gastrointestinal stromal tumors registered, 12 were colorectal (6%). The number of colonic tumors surpassed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…With larger tumors, preoperative treatment should first be considered, and the rate of pancreaticoduodenectomy should be minimized. The degree of malignancy of colorectal stromal tumors is higher than that of small intestine and gastric stromal tumors[ 24 ], and the risk of recurrence is the highest. GISTs generally occur most frequently in middle-aged and elderly people, and the most common onset is between 50 and 70 years old[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…With larger tumors, preoperative treatment should first be considered, and the rate of pancreaticoduodenectomy should be minimized. The degree of malignancy of colorectal stromal tumors is higher than that of small intestine and gastric stromal tumors[ 24 ], and the risk of recurrence is the highest. GISTs generally occur most frequently in middle-aged and elderly people, and the most common onset is between 50 and 70 years old[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, colorectal GISTs remain a predicament for clinicians and scientists to predict clinical behavior. Previous studies have reported the prognostic factors affecting prognosis in the patients with colorectal GISTs, but the majority of the published literature concerning the characteristics, incidence, survival, and treatment strategies of colorectal GISTs has been case reports or small case series (7,(36)(37)(38). Although these findings advanced our understanding of colorectal GISTs, they may be particularly susceptible to patient selection bias and institutional bias, and there is still a voracious need for more information on this uncommon malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their incidence in the esophagus and the duodenum, GISTs situated in the colorectum are similarly rare. Compared with the left colon, GISTs tend to occur in the right side ( 85 ). All colon GISTs are recommended to be surgically resected regardless of tumor size and malignancy degree ( 86 ).…”
Section: Surgical Management In Gastrointestinal Stromal Tumorsmentioning
confidence: 99%